Awans cywilizacyjny i społeczny polskiego robotnika w epoce gierkowskiej. Mit a rzeczywistość = Social and civilizational advance of polish worker in Gierek`s decade. Myth and reality - Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article is abort Social and civilizational advance of polish worker in 1971-1980. It shows processes of propaganda of communist party and the state and stereotypes about those social group. It tooks plots about payment, relationships in families, leisure time, social pathologies, and partici- pation in culture.
Keywords: awans cywilizacyjny; robotnicy - 20 w.; PRL; civilizational advance; workers; Poland; 20 w.